Alternativas de diseño sismoresistente para “el proyecto de edificación Caguano Torres” - Caguano Torres, Patricio Gabriel (2017)
The project presents the technical and economic feasibility of two construction systems, reinforced concrete and structural masonry, which will be evaluated with parameters and requests established in Ecuador; We compare the performance and behavior of each procedure in relevance to the seismic effects of the country and its application in structures of medium height, with geometric variability. The reinforced concrete system with ribbed slabs is based on calculations and parameters established by the NEC 15 codes (chapters of non-seismic loads, seismic design and reinforced concrete) and ACI 318S-14 (foundation chapters, columns, beams and slabs); The structural model was performed in the programs Etabs v15.2.0 and Safev 14.1.1. The unit prices and budgets necessary for the execution of the building were determined, using the current prices of the manual of the CAMICON Construction Industry Chamber 2016. The construction system of structural masonry is based on calculations and parameters defined in the Ecuadorian standards of construction NEC 15 (chapters of non-seismic loads, seismic design and structural masonry); The analysis and evaluation of the architecture is made based on its geometry, constructive process and efficiency of the system. The most optimum alternative was selected for the building under study, the reinforced concrete system being the one best suited to architectural characteristics and demands; For the same the schedules and technical specifications necessary for its execution were realized. Obtaining conclusions and recommendations during the development of this technical work.